AN ESP COURSE DESIGN FOR POSTGRADUATE STUDENTS OF ENGINEERING AT BADJI MOKHTAR ANNABA UNIVERSITY - Amel AFIA; Naouel Abdellatif Mami (My University, 2020)
This paper aims at designing a technical English course for postgraduate students of Engineering at Badji Mokhtar Annaba University. The course design is based on thorough needs analysis taking into consideration needs analysis concepts forwarded by Hutchinson and Waters (1987) and Dudley-Evans and St.Johns (1998). Through a pilot study, the postgraduate students of engineering at Badji Makhtar Annaba university declared that they need to have courses in technical English in order to read and understand the newly updated researches in English, to take part in classroom discussions and to be able to write their own final doctoral project article without referring to experts for the translation from French into English. Thus English for Specific Purposes (ESP) course design is expected to be beneficial to the aforementioned group of learners. The needs analysis in this action research was conducted through the use of different tools. The results revealed that all postgraduate students of Engineering need to learn an ESP course for the development of the predominant skills of reading and writing first, followed by speaking and listening and translation as a fifth skill.